NeutrobodyPlex—monitoring SARS‐CoV‐2 neutralizing immune responses using nanobodies. (27th April 2021) - Wagner, Teresa R; Ostertag, Elena; Kaiser, Philipp D; Gramlich, Marius; Ruetalo, Natalia; Junker, Daniel; Haering, Julia; Traenkle, Bjoern; Becker, Matthias; Dulovic, Alex; Schweizer, Helen; Nueske, Stefan; et al.
Abstract: In light of the COVID‐19 pandemic, there is an ongoing need for diagnostic tools to monitor the immune status of large patient cohorts and the effectiveness of vaccination campaigns. Here, we present 11 unique nanobodies (Nbs) specific for the SARS‐CoV‐2 spike receptor‐binding domain (RBD), of which 8 Nbs potently inhibit the interaction of RBD with angiotensin‐converting enzyme 2 (ACE2) as the major viral docking site. Following detailed epitope mapping and structural analysis, we select two inhibitory Nbs, one of which binds an epitope inside and one of which binds an epitope outside the RBD:ACE2 interface. Based on these, we generate a biparatopic nanobody (bipNb) with viral neutralization efficacy in the picomolar range. Using bipNb as a surrogate, we establish a competitive multiplex binding assay ("NeutrobodyPlex") for detailed analysis of the presence and performance of neutralizing RBD‐binding antibodies in serum of convalescent or vaccinated patients. We demonstrate that NeutrobodyPlex enables high‐throughput screening and detailed analysis of neutralizing immune responses in infected or vaccinated individuals, to monitor immune status or to guide vaccine design. SYNOPSIS: Nanobodies specific for the SARS‐CoV‐2 spike receptor‐binding domain that inhibit its interaction with ACE2 are generated. Nbs binding inside and outside the RBD:ACE2 interface form biparatopic Nbs for serological SARS‐CoV‐2 antibody testing. A multiplex binding assay is presented for high‐throughput detection of neutralizing antibodies in patient samples. NeutrobodyPlex allows for the detailed classification of individuals' neutralization potency. This study describes the generation of biparatopic nanobodies as surrogates for monitoring neutralizing immune responses in SARS‐CoV‐2 infected individuals. NeutrobodyPlex enables high‐throughput screening and detailed analyses of infected or vaccinated individuals. Abstract : This study describes the generation of biparatopic nanobodies as surrogates for monitoring neutralizing immune responses in SARS‐CoV‐2 infected individuals. NeutrobodyPlex enables high‐throughput screening and detailed analyses of infected or vaccinated individuals.